Voltage‐dependent anion channels (VDACs, porin) expressed in the plasma membrane regulate the differentiation and function of human osteoclasts. (19th November 2012) - Kotake, Shigeru; Yago, Toru; Kawamoto, Manabu; Nanke, Yuki
Abstract Fewer molecules have been identified on human than murine osteoclasts, the former differing from murine osteoclasts in many ways. We show that voltage‐dependent anion channels (VDACs, porin) are expressed in the plasma membrane of human osteoclasts. A search for novel proteins expressed in the plasma membrane of human osteoclasts identified VDAC. Anti‐VDAC antibodies inhibited human osteoclastogenesis in vitro. VDAC expression was detected in membranes by immunoelectron microscopy and immunocytochemical double staining. The VDAC protein functions as a Cl− channel. VDACs regulate bone resorption, which show using Osteologic™ plates. The epitope of the antibody lay within a 10‐amino acid sequence in the VDAC. The findings suggest that the VDAC is, at least partly, a novel Cl− channel regulating the differentiation and function of human osteoclasts. VDACs may play a crucial role in acidifying the resorption lacunae between osteoclasts and bone. Inhibitors of VDACs could be used to treat diseases involving increased resorption, such as osteoporosis, rheumatoid arthritis, and Paget's disease.